Promoting Quality Elementary Education The Role of Local Self-Government - Ramadas, V. (JOURNAL OF INDIAN EDUCATION, 2013)
The present paper reports the findings of a research study that explores the role of local self-government in promoting quality of elementary education in Kerala. Adopting survey and case study methods the investigation brought in to highlight twelve categories of indicators that local self-governments grounded their interventions in the field of school education. The local selfgovernments provide strong support for infrastructure development and academic programmes of schools. The programmes and activities of the schools are formulated, planned and implemented under the control, supervision and guidance of Panchayat Education Committees and Block Resource Centers. Contribution of the local self-governments in the academic domain is confined to resource supports for various programmes initiated by SSA. However, there are gram panchayats that adopt micro level planning for enhancing the quality of school education in a comprehensive way by considering all aspects of school life.